2021
DOI: 10.1111/hiv.13223
|View full text |Cite
|
Sign up to set email alerts
|

Failure to return pillbox is a predictor of being lost to follow‐up among people living with HIV on antiretroviral therapy in rural Tanzania

Abstract: Objectives Pill count is used to assess drug adherence in people living with HIV (PLHIV). Carrying a pillbox is associated with fear of concealment and stigma and might indicate poor adherence and predict someone who will be lost to follow‐up (LTFU). We therefore assessed the association between pillbox return and being LTFU in rural Tanzania. Methods This is a nested study of the Kilombero and Ulanga Antiretroviral Cohort (KIULARCO). We included PLHIV aged ≥ 18 years enrolled in KIULARCO between January 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…We did not ascertain treatment failure as an outcome of LTFU from ART care using CD4 counts and viral load counts. However, a strong link between LTFU and treatment failure published in various studies in Tanzania and elsewhere provide justification for addressing LTFU among adolescents [ 25 , 47 ]. Also, we were not able to assess if adolescents presented for care at other clinics during the two-year follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…We did not ascertain treatment failure as an outcome of LTFU from ART care using CD4 counts and viral load counts. However, a strong link between LTFU and treatment failure published in various studies in Tanzania and elsewhere provide justification for addressing LTFU among adolescents [ 25 , 47 ]. Also, we were not able to assess if adolescents presented for care at other clinics during the two-year follow-up time.…”
Section: Discussionmentioning
confidence: 99%
“…9 In 2019, a study in Tanzania found LTFU among PLHIV to be 35.6% at 33 months since the initiation of ART care. 10 Men are more likely to be lost and less likely to be retained in care and achieve virological suppression than women. [11][12][13][14][15] This likelihood may be partly influenced by social norms which make them unable to express their feelings towards their health needs.…”
Section: Introductionmentioning
confidence: 99%